The Importance of Bequests and Life-Cycle Saving in Capital Accumulation: A New Answer - Dynan, Karen E; Skinner, Jonathan; Zeldes, Stephen P (American Economic Review, 2002)
The Importance of Bequests and Life-Cycle Saving in Capital Accumulation: A New Answer by Karen E. Dynan, Jonathan Skinner and Stephen P. Zeldes. Published in volume 92, issue 2, pages 274-278 of American Economic Review, May 2002